(untitled) (International journal of artificial intelligence, 2025)
This article broadly covers the methodological foundations of developing students' professional competence in the process of academic mobility. Academic mobility is analyzed not only as a means of deepening theoretical knowledge, but also as an important factor in the formation of practical skills, communicative culture, independent decision-making, creative approach and effective use of information technologies in students. The article also examines the methodological mechanisms used in the development of students' professional competence based on international experience, their impact on the quality of education and their contribution to the integration of the higher education system of Uzbekistan into the global educational arena. The role of academic mobility in personal, professional and social development, its importance as a priority area in state policy and its role in ensuring the competitiveness of the future generation are emphasized.